Faulting and off‐axis submarine massive sulfide accumulation at slow spreading mid‐ocean ridges: A numerical modeling perspective. (26th June 2017) - Andersen, C.; Theissen‐Krah, S.; Hannington, M.; Rüpke, L.; Petersen, S.
Abstract: The potential of mining seafloor massive sulfide deposits for metals such as Cu, Zn, and Au is currently debated. One key challenge is to predict where the largest deposits worth mining might form, which in turn requires understanding the pattern of subseafloor hydrothermal mass and energy transport. Numerical models of heat and fluid flow are applied to illustrate the important role of fault zone properties (permeability and width) in controlling mass accumulation at hydrothermal vents at slow spreading ridges. We combine modeled mass‐flow rates, vent temperatures, and vent field dimensions with the known fluid chemistry at the fault‐controlled Logatchev 1 hydrothermal field of the Mid‐Atlantic Ridge. We predict that the 135 kilotons of SMS at this site (estimated by other studies) can have accumulated with a minimum depositional efficiency of 5% in the known duration of hydrothermal venting (58, 200 year age of the deposit). In general, the most productive faults must provide an efficient fluid pathway while at the same time limit cooling due to mixing with entrained cold seawater. This balance is best met by faults that are just wide and permeable enough to control a hydrothermal plume rising through the oceanic crust. Model runs with increased basal heat input, mimicking a heat flow contribution from along‐axis, lead to higher mass fluxes and vent temperatures, capable of significantly higher SMS accumulation rates. Nonsteady state conditions, such as the influence of a cooling magmatic intrusion beneath the fault zone, also can temporarily increase the mass flux while sustaining high vent temperatures. Key Points: Numerical modeling combined with vent fluid chemistry data predicts the optimal conditions for accumulation of large SMS deposits Faults must be just wide and permeable enough to control the flow of rising hydrothermal fluids while limiting cooling due to mixing An energy input higher than the one for slow spreading ridges as well as magmatic intrusions give the potential to form large SMS deposits